Analisis Pola Asuh Orang Tua terhadap Keterampilan Berbicara Siswa Kelas IV di Sekolah Dasar - Siti Fariha; Prabawati Nurhabibah; Widia Nur Jannah (CV. ULIL ALBAB CORP, 2024)
This study is motivated by students' speaking skills in the context of classroom learning and analysis of the application of parenting patterns which aims to determine the effect of parenting patterns on the speaking skills of fourth grade students of SDN 5 Arjawinangun. This research uses descriptive qualitative methods. Data collection techniques in this study used observation, interviews and oral tests. This technique uses three stages, namely data reduction, data display and drawing conclusions. The results showed that the parenting pattern applied to parents of students in class IV SDN 5 Arjawinangun is more dominant in using permissive parenting where this parenting pattern is based on hereditary parenting from ancient parents, the obstacles faced are that there are some parents who do not take part in shaping attitudes or shaping student character, then the background of parents' lives is also different, in the home environment there is still a lack of special attention to children in developing students' speaking skills, because these parents feel that they have enough lessons at school so that there is no special monitoring from the parents when they are in the home environment.